Meeting the Challenge of Energy - Konda Reddy, C. V. (Indian Forester, 1981)
While the non-renewable resources of energy is becoming scarcer, the demand for energy is expanding at a very fast rate because of increase in population and industrialization. It is suggested that intensifield social forestry activities can alleviate tbe threating energy crisis. Case studies of cooperation between Forest Departments, Industries and the people in raiSing energy plantations are mentioned.